PENGARUH PENERAPAN SISTEM AKUNTANSI PEMERINTAH DAERAH, SISTEM PELAPORAN, DAN KETAATAN PADA PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DAERAH - Winda Muslimah; Taufeni Taufik; Rusli Rusli (Jurnal Kajian Akuntansi dan Auditing, 2023)
This study aims to determine the effect of the local government accounting system implementation, reporting system, and compliance with laws and regulations on the performance accountability of local government institutions. The data used in this study is primary data using the questionnaire method. The questionnaire method is to distribute a list of question (questionnaires) that will be answered and answered by the respondents, namely the parties who carry out the function of the head of the section in the local government. The research sample was 90 people. The speculation is used the use of multiple linear regression analysis. The effects of the look at suggest that the utility of the nearby government accounting device has an wonderful impact at the accountability of the overall performance of government institutions. The reporting system positive effects the accountibility of the performance of local government institutions, and compliance with laws and regulations positive effects the accountability of the performance of local government institutions.